2020
DOI: 10.3390/cancers12113353
|View full text |Cite
|
Sign up to set email alerts
|

BH3 Mimetics for the Treatment of B-Cell Malignancies—Insights and Lessons from the Clinic

Abstract: The discovery of the link between defective apoptotic regulation and cancer cell survival engendered the idea of targeting aberrant components of the apoptotic machinery for cancer therapy. The intrinsic pathway of apoptosis is tightly controlled by interactions amongst members of three distinct subgroups of the B-cell lymphoma 2 (BCL2) family of proteins. The pro-survival BCL2 proteins prevent apoptosis by keeping the pro-apoptotic effector proteins BCL2-associated X protein (BAX) and BCL2 homologous antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 142 publications
(188 reference statements)
1
10
0
Order By: Relevance
“…Cytochrome c is then released from the mitochondria and activates the caspase cascade, initiating the apoptotic process. 31–34 The present study showed that engeletin maintained mitochondrial membrane potential and alleviated chondrocyte apoptosis by upregulating Bcl-2 expression and inhibiting Bax expression.…”
Section: Discussionsupporting
confidence: 50%
“…Cytochrome c is then released from the mitochondria and activates the caspase cascade, initiating the apoptotic process. 31–34 The present study showed that engeletin maintained mitochondrial membrane potential and alleviated chondrocyte apoptosis by upregulating Bcl-2 expression and inhibiting Bax expression.…”
Section: Discussionsupporting
confidence: 50%
“…Since the approval of venetoclax for chronic lymphocytic leukemia, BH3 mimetics have bloomed as potential treatments for multiple types of cancer, predominantly hematological ( Valentin et al, 2018 ). Despite impressive experimental and clinical results as single agents, increasing evidence showed that BH3 mimetics real potential is enhancing other anti-cancer agents, both conventional chemotherapy and targeted ( Montero and Letai, 2018 ; Oudenaarden et al, 2018 ; Savona and Wei, 2019 ; Lin et al, 2020 ). Numerous studies have demonstrated that cancer cells often rely on anti-apoptotic proteins to acquire resistance to therapy, and BH3 mimetics can effectively block these adaptations ( Hata et al, 2015 ; Maji et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of BCL2 and of other members of the BCL2 family is well-described in follicular lymphoma (FL), chronic lymphocytic leukemia (CLL), mantle cell lymphoma (MCL), and in acute myeloid leukemia (AML) 3 , 4 . Mimicking proapoptotic BH3-only proteins, BH3 mimetics antagonize the function of antiapoptotic BCL2 family proteins, providing a new opportunity for treatment of these diseases 3 , 4 . Antagonizing BCL2, venetoclax was the first BH3 mimetic approved for CLL and then—in combination with hypomethylating drugs—also for AML 1 , 5 .…”
Section: Introductionmentioning
confidence: 99%